Odpowiedzi

Najlepsza Odpowiedź!
2010-03-14T18:01:49+01:00
6x=3 / : 6
x = ³/₆
x= ½

-3x=7 / : (-3)
x = - ⁷/₃
x = - 2 ⅓

22x=1/5 / : 22
x = ¹/₅ *¹/₂₂
x = ¹/ ₁₁₀

1,2x=4,8 / : 1,2
x = 4

1/3x=3 / *3
x = 9

-3/5x=-5 / * (-⁵/₃)
x = ²⁵/₃
x = 8 ⅓

3/4x=-4/9 / * ⁴/₃
x = - ¹⁶/₂₇

0,1x=-7 / : 0,1
x = -70

-3x=2x-10
-3x-2x = -10
-5x = -10 / :(-5)
x = 2

2x-2=7-x
2x+x = 7+2
3x = 9 / :3
x = 3

10=4-2x
2x = 4-10
2x = -6 / :2
x = -3

-(2x-1)=4
-2x+1 = 4
-2x = 4-1
-2x = 3 / : (-2)
x = - ³/₂
x = -1 ½

2(+1)=6x
2 = 6x / : 6
x = ²/₆
x = ⅓

-(4+x)=2(3-x)
-4-x = 6 - 2x
-x+2x = 6+4
x = 10
2010-03-14T18:08:44+01:00
A.6x=3/:6
x=3/6=1/2
b.-3x=7/:(-3)
x=-7/3=-2całe i 1/3
c.22x=1/5/:22
x=1/5*1/22
x=1/110
d.1,2x=4,8/:1,2
x=4
e.1/3x=3/:1/3
x=1
f.-3/5x=-5i3/4x=-4/9
-3,5x+5i3,4x=-4,9
-3,5+23,4x=-4/9
19,9x=-4/9/:19,9
x=-0,24
g.0,1x=-7/:0,1
x=-70
h.-3x=2x-10
-3x-2x=10
-5x=10/:-5
x=-2
i.2x-2=7-x
2x+x=2+7
3x=9/:3
x=3
J.10=4-2x
2x=-10+4
2x=-6/:2
x=-3
K.-(2x-1)=4
-2x=-1+4
-2x=3/:-2
x=-3/2
L.2(+1)=6x
-6x=-3/:-6
x=1/2


2010-03-14T18:09:58+01:00
6x=3/6
x=0,5

-3x=7/-3
x=-2 i jedna trzecia

22x=(1/5)/22
x=1/5*1/22
x=1/110

1,2x=4,8/1,2
x=4

1/3x=3/(1,3)
x=2 i szesc trzynastych


-3/5x=-5 3/4x=-4/9

0,1x=-7/0,1
x=-70

-3x=2x-10
-3x-2x=-10
-5x=-10/-5
x=2

2x-2=7-x
2x+x=7+2
3x=9/3
x=3

10=4-2x
10-4=-2x
6=-2x
-2x=6/-2
x=-3

-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3/-2
x=-1,5

2(+1)=6x
6x=3/6
x=1,5

-(4+x)=2(3x+5)=3
-4-x=6x+10...

w tym ostatnim przykladzie nie wiem o co chodzi